Peranan kelompok tani dalam pembagian pupuk bersubsidi di Desa Pasar Melintang, Deli Serdang - Pakpahan, Helena Tatcher; Hutapea, Kenal P; Simbolon, Polma Risma (Universitas Musamus, Merauke, Papua, 2023)
Increasing the productivity of rice plants requires the role of fertilizer, one of which is lowland rice farmers who believe that fertilizer is the most important key factor for increasing rice production. The government's role is to provide subsidized fertilizers for the agricultural sector. Farmer groups were formed to solve problems faced by farmers that cannot be solved individually. The role of farmer groups in distributing subsidized fertilizers is to facilitate the distribution of subsidized fertilizers into the hands of farmers. Subsidized fertilizers are only intended for farmers who join farmer groups, this is in accordance with the Regulation of the Minister of Agriculture Number 47 of 2017 concerning the designation and highest retail price (HET) of subsidized fertilizers. This study aims to analyze the role of farmer groups in distributing subsidized fertilizers. The research method uses the Descriptive Analysis method, which is to explain and describe the phenomena that occur in the research area and to analyze the role of farmer groups in distributing subsidized fertilizer. The results of this study are that the role of farmer groups in distributing subsidized fertilizers is included in the high category with a total score of 2.9 in the role category. Farmer groups play an important role in improving farmer performance with changes in farmers towards a better way of managing lowland rice farming as indicated by the existence of learning classes that increase farmer knowledge, a vehicle for cooperation that builds cooperation in the distribution of subsidized fertilizers and production units helping farmers with get subsidized fertilizer.